2020
DOI: 10.1108/ramj-01-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and job satisfaction among nurses in government tertiary hospitals in Nigeria

Abstract: Purpose Job satisfaction is indispensable in the daily life of the workforce, and the mechanism that drives job satisfaction requires the attention of the management of corporate organisations. The purpose of this paper is to investigate the predictors of work environment on job satisfaction among nurses in both federal and state tertiary hospitals in Lagos State. Design/methodology/approach The study used the longitudinal research design to elicit information from the respondents. The research instrument us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 48 publications
13
57
0
3
Order By: Relevance
“…To add on, a research by Sunarsi (2019) has also found that the work environment has a positive and significant impact on work satisfaction. Similarly, Akinwale & George (2020) discovered that all variables of work environment influenced job satisfaction. Al-Hamdan, Manojlovich, & Tanima (2017) concluded that the work environment was positively associated with job satisfaction.…”
Section: Results Of Hypothesis Testingmentioning
confidence: 96%
See 1 more Smart Citation
“…To add on, a research by Sunarsi (2019) has also found that the work environment has a positive and significant impact on work satisfaction. Similarly, Akinwale & George (2020) discovered that all variables of work environment influenced job satisfaction. Al-Hamdan, Manojlovich, & Tanima (2017) concluded that the work environment was positively associated with job satisfaction.…”
Section: Results Of Hypothesis Testingmentioning
confidence: 96%
“…Similarly, a research by Sunarsi (2019) found that the work environment has a positive and significant impact on work satisfaction. Likewise, Akinwale & George (2020) discovered that all variables of work environment influenced job satisfaction. The researchers conducted the study on work environment and job satisfaction among nurses in hospitals in Nigeria.…”
Section: Work Environmentmentioning
confidence: 99%
“…In Saudi Arabia, entrepreneurship is considered to be one of the key elements of the country's developmental prospects (Akinwale & George, 2020). The kingdom's youth are encouraged to pick up entrepreneurship and are offered youth awards as incentive (Alessa & Alajmi, 2017).…”
Section: Digest Of Middle East Studiesmentioning
confidence: 99%
“…Recent studies about organisational justice maintain that distributive justice and procedural justice may function as a significant enabler of employee outcomes, particularly job satisfaction in organisations (Hao et al, 2016;Hur & Ha, 2019;Singhry, 2018). More recent studies reveal that job satisfaction is a critical phenomenon in certain environments, such as organisational settings (Tran, 2019), workplace diversity (Hauret & Williams, 2020), health care organisation (Akinwale & George, 2020) and occupation categories (Andrade & Westover, 2019). From an employee's perspective, job satisfaction is obtained after assessing job conditions (e.g., according to different occupation types) and their like or dislike of the job (Robbins & Judge, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, if employees like their intrinsic job features (e.g., achievement, recognition, responsibility, advancement and growth) and extrinsic job features (e.g., organisation policies, supervisor, coworker, pay, status and security) this attitude may result in higher job satisfaction. In contrast, if employees dislike some job features, this attitude may bring about a lower job satisfaction (Akinwale & George, 2020;Azman & Mohd Ridwan, 2016;Fabi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%